PENGARUH SUPERVISI PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA SMPN 9 JAKARTA - Nurmawati, Nurmawati; Ilfa, Eka Farulia (Jurnal Akrab Juara, 2019)
This study aims to determine the effect of supervision of learning on student learning outcomes. The study was designed in 3 cycles, each of which consisted of planning, implementing, observing, reflecting, and revising activities. The action taken is supervision, followed by collection of cooperation and creativity. The data collection method used is descriptive method. The results of the study, quantitatively indicate an increase in student learning outcomes from cycles 1, 2, and 3. In cycle 2, so also in the cycle 3. Based on the data from the action results from cycle to cycle, there appears to be a change or development from cycle 1 to cycle 2 and from cycle 2 to cycle 3. If in cycle 1, the number of students who get grades reaches KKM there are 10 people or 28.57%, then in cycle 2, the number of students who score reaches KKM increases by 3 people to 13 students or 37, 15%. Furthermore, in the third cycle the number of students who got the score reached KKM increased by 7 people, so that the total number of students who had scored reached KKM up to cycle 3, to 20 people or 57%.